Variation of tsetse fly abundance in relation to habitat and host presence in the Maasai Steppe, Tanzania. Issue 1 (June 2017) - Ngonyoka, Anibariki; Gwakisa, Paul S.; Estes, Anna B.; Nnko, Happiness J.; Hudson, Peter J.; Cattadori, Isabella M.
ABSTRACT: Human activities modify ecosystem structure and function and can also alter the vital rates of vectors and thus the risk of infection with vector‐borne diseases. In the Maasai Steppe ecosystem of northern Tanzania, local communities depend on livestock and suitable pasture that is shared with wildlife, which can increase tsetse abundance and the risk of trypanosomiasis. We monitored the monthly tsetse fly abundance adjacent to Tarangire National Park in 2014–2015 using geo‐referenced, baited epsilon traps. We examined the effect of habitat types and vegetation greenness (NDVI) on the relative abundance of tsetse fly species. Host availability (livestock and wildlife) was also recorded within 100×100 m of each trap site. The highest tsetse abundance was found in the ecotone between Acacia‐Commiphora woodland and grassland, and the lowest in riverine woodland. Glossina swynnertoni was the most abundant species (68%) trapped throughout the entire study, while G. pallidipes was the least common (4%). Relative species abundance was negatively associated with NDVI, with greatest abundance observed in the dry season. The relationship with the abundance of wildlife and livestock was more complex, as we found positive and negative associations depending on the host and fly species. While habitat is important for tsetse distribution, hosts also play a critical role in affecting fly abundance and, potentially, trypanosomiasis risk.